The erbB-2 mitogenic signaling pathway: tyrosine phosphorylation of phospholipase C-gamma and GTPase-activating protein does not correlate with erbB-2 mitogenic potency. - Fazioli, F (1991)
The erbB-2 gene product, gp185erbB-2, unlike the structurally related epidermal growth factor (EGF) receptor (EGFR), exhibits constitutive kinase and transforming activity. We used a chimeric EGFR/erbB-2 expression vector to compare the mitogenic signaling pathway of the erbB-2 kinase with that of the EGFR, at similar levels of expression, in response to EGF stimulation. The EGFR/erbB-2 chimera was significantly more active in inducing DNA synthesis than the EGFR when either was expressed in NIH 3T3 cells. Analysis of biochemical pathways implicated in signal transduction by growth factor receptors indicated that both phospholipase C type gamma (PLC-gamma) and the p21ras GTPase-activating protein (GAP) are substrates for the erbB-2 kinase in NIH 3T3 fibroblasts. However, under conditions in which activation of the erbB-2 kinase induced DNA synthesis at least fivefold more efficiently than the EGFR, the levels of erbB-2- or EGFR-induced tyrosine phosphorylation of PLC-gamma and GAP were comparable. In addition, the stoichiometry of tyrosine phosphorylation of these putative substrates by erbB-2 appeared to be at least an order of magnitude lower than that induced by platelet-derived growth factor receptors at comparable levels of mitogenic potency. Thus, our results indicate that differences in tyrosine phosphorylation of PLC-gamma and GAP do not account for the differences in mitogenic activity of the erbB-2 kinase compared with either the EGFR or platelet-derived growth factor receptor in NIH 3T3 fibroblasts.